2013
DOI: 10.1097/hco.0b013e32835b0b17
|View full text |Cite
|
Sign up to set email alerts
|

The importance of increased percentage of biventricular pacing to improve clinical outcomes in patients receiving cardiac resynchronization therapy

Abstract: Every effort should be made in all patients receiving CRT to approach 100% BIV pacing by a correct device programming, a correct pharmacologic regimen and atrioventricular nodal ablation in atrial fibrillation patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
(7 reference statements)
1
5
0
Order By: Relevance
“…Loss of biventricular pacing can occur as a result of a long AVD due to intrinsic atrioventricular conduction. In such patients, shortening of AVD may increase the degree of biventricular pacing [24][25][26]. In the present study, patients in whom the AVD was changed Taken together, the present findings support the role of systematic AVD optimization to achieve the highest possible percentage of biventricular stimulation and improve hemodynamic parameters.…”
Section: A High Percentage Of Biventricular Pacing Is Associated Withsupporting
confidence: 80%
See 1 more Smart Citation
“…Loss of biventricular pacing can occur as a result of a long AVD due to intrinsic atrioventricular conduction. In such patients, shortening of AVD may increase the degree of biventricular pacing [24][25][26]. In the present study, patients in whom the AVD was changed Taken together, the present findings support the role of systematic AVD optimization to achieve the highest possible percentage of biventricular stimulation and improve hemodynamic parameters.…”
Section: A High Percentage Of Biventricular Pacing Is Associated Withsupporting
confidence: 80%
“…CRT patients [24]. Koplan et al [25] demonstrated that the greatest benefit in reduction of HF hospitalization and all-cause mortality was achieved with a biventricular pacing above 92%.…”
Section: A High Percentage Of Biventricular Pacing Is Associated Withmentioning
confidence: 99%
“…The biventricular pacing percentage was determined as the average delivery of biventricular pacing percentage throughout the follow-up time at the last available device interrogation. Two groups were selected as representing high ($97%) and low (<97%) biventricular pacing, on the basis of a recent literature review and results from the MADIT-CRT trial evaluating the cutoff point of biventricular pacing efficacy on HF/death and death (5,8,12). The likelihood of receiving low biventricular pacing (defined as <97%) was raised with increasing burden of ectopic beats at baseline (Figures 2 and 3).…”
Section: Device Programming and Interrogationmentioning
confidence: 99%
“…The margin of success associated with implantation of a CRT device, however, relies on the capability to effectively deliver biventricular pacing, and even minor reductions in biventricular pacing can diminish the beneficial effects of CRT (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…It is important to highlight that differences in pacing delivery may impact patient outcomes. For example, analyses have also shown that reductions in percentage of pacing can impact outcomes, including heart failure hospitalizations and mortality 15,28. More detailed results from the Adaptive CRT trial specifically quantified the incremental benefit for each percentage point increase in %LV pacing 23.…”
Section: Discussionmentioning
confidence: 99%